Protein O-mannosylation: what we have learned from baker's yeast - Loibl, Martin; Strahl, Sabine (Biochimica et biophysica acta. Molecular cell research, 2013)
Background: Protein O-mannosylation is a vital type of glycosylation that is conserved among fungi, animals, and humans. It is initiated in the endoplasmic reticulum (ER) where the synthesis of the mannosyl donor substrate and the mannosyltransfer to proteins take place. O-mannosylation defects interfere with cell wall integrity and ER homeostasis in yeast, and define a pathomechanism of severe neuromuscular diseases in humans. Scope of review: On the molecular level, the O-mannosylation pathway and the function of O-mannosyl glycans have been characterized best in the eukaryotic model yeast Saccharomyces cerevisiae. In this review we summarize general features of protein O-mannosylation, including biosynthesis of the mannosyl donor, characteristics of acceptor substrates, and the protein O-mannosyltransferase machinery in the yeast ER. Further, we discuss the role of O-mannosyl glycans and address the question why protein O-mannosylation is essential for viability of yeast cells. General significance: Understanding of the molecular mechanisms of protein O-mannosylation in yeast could lead to the development of novel antifungal drugs. In addition, transfer of the knowledge from yeast to mammals could help to develop diagnostic and therapeutic approaches in the frame of neuromuscular diseases. This article is part of a Special Issue entitled: Functional and structural diversity of endoplasmic reticulum.
Gesehen am 15.05.2017